1994
DOI: 10.1177/002221949402700404
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Substance Use

Abstract: A considerable body of literature has accumulated that examines patterns of substance use and abuse among adolescents attending general education classes. However, much less information exists on the prevalence and predictors of substance use among adolescents with learning disabilities. One purpose of this study was to determine the comparative prevalence of tobacco, alcohol, and marijuana use among a sample of 123 students with learning disabilities (91 male and 32 female, mean age = 14.37 years) and 138 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Research indicates that individuals with SLDs are more likely to engage in negative health behaviors, such as smoking tobacco and cannabis, when compared with their peers without learning difficulties, although those with SLDs do not seem to have an increased risk of alcohol use (Finn, Lopata, & Marable, 2010; Maag, Irvin, Reid, & Vasa, 1994). People who attempt suicide often exhibit a range of substance problems (Borges, Walters, & Kessler, 2000), including smoking (Bronisch, Höfler, & Lieb, 2008) and cannabis abuse (Beautrais, Joyce, & Mulder, 1999).…”
mentioning
confidence: 99%
“…Research indicates that individuals with SLDs are more likely to engage in negative health behaviors, such as smoking tobacco and cannabis, when compared with their peers without learning difficulties, although those with SLDs do not seem to have an increased risk of alcohol use (Finn, Lopata, & Marable, 2010; Maag, Irvin, Reid, & Vasa, 1994). People who attempt suicide often exhibit a range of substance problems (Borges, Walters, & Kessler, 2000), including smoking (Bronisch, Höfler, & Lieb, 2008) and cannabis abuse (Beautrais, Joyce, & Mulder, 1999).…”
mentioning
confidence: 99%
“…The above average risk subsample was recruited from remedial education classrooms of rural and urban schools. Remedial program placements were based on poor performance in reading, mathematics or both, which correlate with behavior problems (Bachman et al, 2008; Martin et al, 2000) as do learning disabilities (Karacostas and Fisher, 1993; Magg et al, 1994). The rural program was for Mexican, migrant, English-as-Second-Language students.…”
Section: Methodsmentioning
confidence: 99%
“…Students with mild academic disabilities are characterized by several behavioral and emotional risk factors, which may put them at higher risk for (problematic) substance use (Borowsky, 1998;Dekker, Koot, van der Ende, & Verhulst, 2002;Einfeld, Ellis, & Emerson, 2011;Totsika, Hastings, Emerson, Lancaster, & Berridge, 2011). However, the scant literature on this topic does not consistently confirm that those with a disability are indeed more likely to use substances, and results appear to differ by type of substance (Fakier & Wild, 2011;Fidler, Michell, Raab, & Charlton, 1992;Katims & Zapata, 1996;Kepper, Monshouwer, Dorsselaer, & Vollebergh, 2011;Maag & Irvin, 1994;Mc-Crystal, Percy, & Higgins, 2007). With respect to alcohol use, the literature is fairly consistent.…”
Section: Introductionmentioning
confidence: 99%
“…abilities are comparable with respect to their alcohol use (Fakier & Wild, 2011;Katims & Zapata, 1996;Kepper et al, 2011;Maag & Irvin, 1994), although one study found that students with a disability reported lower levels of alcohol use compared to those without disabilities (McCrystal et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation